Evaluation of food safety related behaviors of retail and food service employees while handling fresh and fresh-cut leafy greens. (September 2016) - Choi, Jihee; Norwood, Hillary; Seo, Soobin; Sirsat, Sujata A.; Neal, Jack
Abstract: Foodborne illness outbreaks are often associated with fresh and fresh-cut produce (specifically leafy greens); however, effective training and methods of prevention have not been readily available for the retail and food service industry. The objective of this study was to assess and evaluate the current state of compliance and employee handling practices for fresh and fresh-cut produce, and to identify factors influencing employees' fresh and fresh-cut handling practices using an observational survey tool. A total of sixteen restaurants and fifteen grocery stores in Texas and Ohio were observed. The results revealed low compliance of employees' leafy green handling practices such as improper use of thermometers, lack of documentation, and poor employee hygiene. Statistical analysis results suggested that employees' food safety behaviors vary based on several factors such as operation size, cuisine, and operation type. The results of the study will provide practical guidelines for training employees handling leafy green produce at fresh and fresh-cut packing facilities, produce distribution centers, grocery stores, and restaurants. Highlights: Employees' leafy green produce handling practices were observed. Results revealed a low compliance rate of food safety behaviors. Improper use of thermometers and poor employee hygiene were observed. Independent t-tests identified factors affecting leafy green handling practices. Employees' handling behaviors varied by operation size/type and cuisine.